2.73+0.06x=13.48-0.14x

Simple and best practice solution for 2.73+0.06x=13.48-0.14x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.73+0.06x=13.48-0.14x equation:



2.73+0.06x=13.48-0.14x
We move all terms to the left:
2.73+0.06x-(13.48-0.14x)=0
We add all the numbers together, and all the variables
0.06x-(-0.14x+13.48)+2.73=0
We get rid of parentheses
0.06x+0.14x-13.48+2.73=0
We add all the numbers together, and all the variables
0.2x-10.75=0
We move all terms containing x to the left, all other terms to the right
0.2x=10.75
x=10.75/0.2
x=53+0.15/0.2

See similar equations:

| -212=-4x-4(6x-10) | | F(x)=2x+11x=5 | | -4.9x^2+29.4+2.5=0 | | 0.75x=18-0.5x | | f−-22=24 | | 12.73+0.06x=13.48-0.14 | | 8(3m+15)=2(m-2) | | 20y2+21y+4=0 | | 5y^2+20y-35=0 | | 2/7x-3+2x=-69/7 | | d+-1=-46 | | |4-4v|=28 | | y-8=9/16-63/16 | | 5b-7b=12 | | -57=3(3x-4) | | 36=2g | | 6n-4-2n=12 | | x^2+11x=155 | | (2/3)p-25=115 | | 8(x+10)=-6(x-8)-1 | | 50x+30(100)=40x+40*100 | | f−98=-84 | | -3s=-9 | | 24-5w=3w | | 3x-8x-11=-5x+8-11 | | 6x+5(x-7)=-167 | | 0=6u | | 12x-2=14x | | 6+5(m+)=26 | | 32-3x=2x-18 | | 4x-x=40 | | 8u+30=13u |

Equations solver categories